2023
DOI: 10.3389/fphar.2023.1017475
|View full text |Cite
|
Sign up to set email alerts
|

Whole β-glucan particle attenuates AOM/DSS-induced colorectal tumorigenesis in mice via inhibition of intestinal inflammation

Abstract: Yeast β-glucan is a polysaccharide purified from the Saccharomyces cerevisiae cell wall, and its multiple biological activities are essential for immune regulation. However, the effect of β-glucan on the intestinal immune response during colitis-associated colorectal cancer (CAC) is unclear. Here, we explore the possible role of β-glucan in the development of CAC. Wild type (WT) mice with CAC induced by azoxmethane (AOM) and dextran sodium sulfate (DSS) had fewer tumors than untreated mice after oral β-glucan … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 63 publications
0
0
0
Order By: Relevance
“…Histopathology is a common method for assessing intestinal inflammation and pathology in animal models, typically revealing moderate to severe dysplasia in the epithelium of mouse tissues treated with AOM/DSS. This is accompanied by irregular crypt arrangement, clear infiltration of inflammatory cells in the mucosa, and the formation of typical tumors in the distal colon [33]. In this histopathological analysis, epithelial cell loss, crypt loss, and adenocarcinoma occurred in the control group; however, these symptoms were alleviated in the broccoli-treated group, especially the NFB group, showing similar features to the normal group.…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…Histopathology is a common method for assessing intestinal inflammation and pathology in animal models, typically revealing moderate to severe dysplasia in the epithelium of mouse tissues treated with AOM/DSS. This is accompanied by irregular crypt arrangement, clear infiltration of inflammatory cells in the mucosa, and the formation of typical tumors in the distal colon [33]. In this histopathological analysis, epithelial cell loss, crypt loss, and adenocarcinoma occurred in the control group; however, these symptoms were alleviated in the broccoli-treated group, especially the NFB group, showing similar features to the normal group.…”
Section: Discussionmentioning
confidence: 63%
“…Owing to the oral administration of broccoli extract to mice with AOM/DSS-induced CRC, it was confirmed that the colon lengthened, the colon weight/length ratio reduced, and the number of tumors reduced. DSS dissolved in drinking water is toxic to the epithelial lining of the large intestine, causing severe colitis, which is characterized by weight loss and bloody stool after DSS ingestion, and causes inflammation in the liver and spleen, causing weight gain [32,33]. Accordingly, in this study, the weight of the liver and spleen of the CON group increased significantly compared with that of the NOR group and was decreased in the groups that consumed broccoli extract.…”
Section: Discussionmentioning
confidence: 64%
“…Additionally, β-glucan enhanced resilience against chronic colitis by remodeling the inflammatory microenvironment. These data suggest that β-glucan can ameliorate experimental intestinal inflammation and delay the progression of CAC ( 80 ). Ji Hyeon Kim and colleagues evaluated the therapeutic potential of LMW-AP-FBGin BALB/c mice implanted with subcutaneous CT-26 colon cancer cells.…”
Section: The Role and Biological Mechanism Of β-Glucan In The Prevent...mentioning
confidence: 85%